The battle to do good : inside McDonald's sustainability journey - Langert, Bob (Emerald Publishing Limited, 2019)
In The Battle to Do Good, former McDonald's executive Bob Langert takes readers on a behind-the-scenes eye witness account of the mega brand's battle to address numerous societal hot-button issues, such as packaging, waste, recycling, obesity, deforestation, and animal welfare. From the late 80s, McDonald's landed smack in the middle of one contentious issue after another, often locking horns with powerful NGOs such as Greenpeace, People for the Ethical Treatment of Animals, and Corporate Accountability. This sudden shift from being the beloved Golden Arches since opening its doors in 1955, to the demon of many societal ills, caught McDonald's off guard. Langert chronicles the highs and lows that McDonald's experienced in turbulent times and how its sustainability journey evolved from playing defense to strategically solving issues with unlikely partners, including a whirling dervish, autistic animal scientist, and avid environmentalists from the World Wildlife Fund and Conservation International. Packed with first-hand anecdotes, interviews with key McDonald's executives and NGO leaders, and scores of lessons learned, The Battle to Do Good is a sustainability page turner that provides unique insights and guidance on how to successfully navigate and manage today's societal issues to make the business stronger, more relevant, and more profitable.
Keywords: McDonald's Corporation.; Fast food restaurants -- United States -- Management.; Social responsibility of business.; Sustainable development.; Business & Economics -- Business Ethics.; Business ethics & social responsibility.; elektronické knihy; electronic books